2013
DOI: 10.1007/s12114-012-9149-z
|View full text |Cite
|
Sign up to set email alerts
|

Racial Position Segregation in Intercollegiate Football: Do Players become more Racially Segregated as they Transition from High School to College?

Abstract: This study revisits the issue of racial position segregation or racial “stacking” in intercollegiate football. Estimating a probit model, we examine the impact that a player's race has on the probability of him changing positions when he moves from high school to the collegiate ranks. Descriptive statistics of our data reveal significant evidence that racial position segregation is widespread in high school football. The data also offers much information about which players are likely to change positions and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Melnick 23 and Norris and Jones 24 ), the results suggest that mean skin tone in wide positions is still slightly darker than in central positions. Although in line with previous research, 9,25 the difference we report is minute and the effect small. The present study also advances the literature by being the first to assess positional differences by skin tone across the population of English professional football.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Melnick 23 and Norris and Jones 24 ), the results suggest that mean skin tone in wide positions is still slightly darker than in central positions. Although in line with previous research, 9,25 the difference we report is minute and the effect small. The present study also advances the literature by being the first to assess positional differences by skin tone across the population of English professional football.…”
Section: Discussionsupporting
confidence: 92%
“…Given the financial resources available in the Premier League, it was thought that clubs would purchase the most suitable candidate for the position. However, this fails to consider that, according to Pitts and Yost, 25 the most suitable candidate may also mean the one who best fits the stereotype. As Melnick 23 (p. 126) states:‘In the absence of any compelling evidence to support the belief that white and black soccer players possess certain physical and/or psychological characteristics which make them better suited for playing particular positions, one must look elsewhere for an explanation of these findings.’…”
Section: Discussionmentioning
confidence: 99%
“…Sack, Singh, and Thiel (2005) described stacking, or occupational segregation, as the assigning of individuals to certain positions based on assumptions regarding one's race. Pitts and Yost (2012) argued that stacking Black athletes into peripheral positions could be dangerous for them if they intend to pursue future leadership positions due to the lack of decision-making skills in peripheral positions. In the context of centrality, stacking makes it harder for non-central position holders to be promoted, or only affords them with poor management options if they are promoted.…”
Section: Centrality and Football Position Assignmentmentioning
confidence: 99%
“…Lavoie (1989) found evidence of positional stacking involving minority (French-Canadian) hockey players. More recently, Pitts and Yost (2013) found position segregation in college football where black high school quarterbacks and white high school running backs were more likely to change positions in college than their white and black counterparts, respectively. Exit Discrmination Johnson and Marple (1973) pioneered a new branch of discrimination research when they found evidence from 1970-71 NBA data that marginal white players had longer careers than marginal black players.…”
Section: Positional Discriminationmentioning
confidence: 99%